Disc–jet coupling changes as a possible indicator for outbursts from GX 339−4 remaining within the X-ray hard state. Issue 1 (31st December 2020) - de Haas, S E M; Russell, T D; Degenaar, N; Markoff, S; Tetarenko, A J; Tetarenko, B E; van den Eijnden, J; Miller-Jones, J C A; Parikh, A S; Plotkin, R M; Sivakoff, G R
ABSTRACT: We present quasi-simultaneous radio, (sub-)millimetre, and X-ray observations of the Galactic black hole X-ray binary GX 339−4, taken during its 2017–2018 outburst, where the source remained in the hard X-ray spectral state. During this outburst, GX 339−4 showed no atypical X-ray behaviour that may act as an indicator for an outburst remaining within the hard state. However, quasi-simultaneous radio and X-ray observations showed a flatter than expected coupling between the radio and X-ray luminosities (with a best-fitting relation of $L_{\rm radio} \propto L_{\rm X}^{0.39 ± 0.06}$ ), when compared to successful outbursts from this system ($L_{\rm radio} \propto L_{\rm X}^{0.62 ± 0.02}$ ). While our 2017–2018 outburst data only span a limited radio and X-ray luminosity range (∼1 order of magnitude in both, where more than 2 orders of magnitude in L X is desired), including data from other hard-only outbursts from GX 339−4 extends the luminosity range to ∼1.2 and ∼2.8 orders of magnitude, respectively, and also results in a flatter correlation (where $L_{\rm radio} \propto L_{\rm X}^{0.46 ± 0.04}$ ). This result is suggestive that for GX 339−4 a flatter radio–X-ray correlation, implying a more inefficient coupling between the jet and accretion flow, could act as an indicator for a hard-only outburst. However, further monitoring of both successful and hard-only outbursts over larger luminosity ranges with strictly simultaneous radio and X-ray observations is required from different single sources to explore if this applies generally to the population of black hole X-ray binaries, or even GX 339−4 at higher hard-state luminosities.